2023
DOI: 10.1111/pai.14043
|View full text |Cite
|
Sign up to set email alerts
|

Oral immunotherapy as a curative treatment for food‐allergic preschool children: Current evidence and potential underlying mechanisms

Lieke J. C. Barten,
Marit Zuurveld,
Joyce Faber
et al.

Abstract: The worldwide rising prevalence of food allergy is a major public health concern. Standard care consists of allergen avoidance and rescue medication upon accidental exposure. Oral immunotherapy (OIT) is increasingly being studied as a treatment option. Although desensitization (an increased reaction threshold) is often achieved during OIT, sustained unresponsiveness (SU; clinical nonreactivity after finishing OIT) is not achieved in most patients. A few studies have investigated the effectiveness of OIT in chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 76 publications
0
9
0
Order By: Relevance
“…3 Diverse clinical trials confirmed the efficacy of e-OIT in inducing desensitization to peanuts. 3 Furthermore, peanut e-OIT in preschoolers exhibited 4 weeks after stopping e-OIT a sustained unresponsiveness (SU) rate of 91% in a randomized trial involving children under 36 months of age, with 70% being under 24 months of age (DEVIL study). 5 The IMPACT study revealed after 26 weeks of avoidance a SU rate of 21% in the e-OIT group versus 2% in the placebo group.…”
Section: Of 3 | Edito Ria Lmentioning
confidence: 95%
See 4 more Smart Citations
“…3 Diverse clinical trials confirmed the efficacy of e-OIT in inducing desensitization to peanuts. 3 Furthermore, peanut e-OIT in preschoolers exhibited 4 weeks after stopping e-OIT a sustained unresponsiveness (SU) rate of 91% in a randomized trial involving children under 36 months of age, with 70% being under 24 months of age (DEVIL study). 5 The IMPACT study revealed after 26 weeks of avoidance a SU rate of 21% in the e-OIT group versus 2% in the placebo group.…”
Section: Of 3 | Edito Ria Lmentioning
confidence: 95%
“…Allergic side effects are common but mostly mild and self-limiting. 3 Diverse clinical trials confirmed the efficacy of e-OIT in inducing desensitization to peanuts. 3 Furthermore, peanut e-OIT in preschoolers exhibited 4 weeks after stopping e-OIT a sustained unresponsiveness (SU) rate of 91% in a randomized trial involving children under 36 months of age, with 70% being under 24 months of age (DEVIL study).…”
Section: Of 3 | Edito Ria Lmentioning
confidence: 95%
See 3 more Smart Citations